"Give me your hands if we be friends": collaborative authority in Shakespeare fan fiction. (2nd July 2016) - Fazel, Valerie; Geddes, Louise
Abstract : Due to the interactive affordances of twenty-first century technologies, the relationship between readers and texts is often repositioned as part of a communal experience of consumption and reproduction. Inclusive in this expanding culture are user-generated adaptations of Shakespeare, most saliently fanfic. The fanfic universe prolifically crosses genres, putting the Shakespearean urtext in conversation with any other object of cultural interest, and occasionally subjugates the Shakespearean text to the dominant popular icon of the moment. Fanfic manifests textual enjoyment as a creative act; the genre is both recreational and re-creational, resulting in new adaptive works that expand the dramas to include sequels, prequels, and off-stage explorations of character and plot. Because Shakespeare is experienced variously through printed text, television, film, theatrical, or digitized performance – all of which underline the instability of an authoritative Shakespeare text – Shakespeare studies is uniquely positioned to expand critical understanding of adaptation and appropriation vis-à-vis the fanfiction universe. Fanfic's online modality, existing on websites that facilitate dialogic interaction between author and audience, offers scholars an ongoing chronicle of reception. Uniquely, online interactions allow Shakespeare cultural critics to analyze the ways user-generated fanfic positions Shakespeare's work as open to transition, crafting adaptations that illustrate what Shakespeare means to everyday users.